DIFFERENCE IN THE LEVELS OF FERRITIN, HEMOGLOBIN, AND ERYTHROCYTE COUNT OF STAGE 5 CHRONIC KIDNEY DISEASE PATIENTS AFTER ONE, THREE AND SIX MONTHS OF HEMODIALYSIS - Wibowo, Subur; Chasani, Shofa; Wibowo, Joko Wahyu; Nasihun, Taufiqurrachman (Sains Medika: Jurnal Kedokteran dan Kesehatan, 2019)
INTRODUCTION: 77,892 chronic kidney disease patients in Indonesia undergo hemodialysis in 2017. However, the effects of period of undergoing hemodialysis on hemoglobin level, erythrocyte count, and ferritin level are still unclear.OBJECTIVE: This research aims at examining the effects of period of undergoing hemodialysis on the levels of ferritin, hemoglobin, and erythrocyte count of stage 5 of chronic kidney disease patients.METHODS: In the analytical observational research with a cross sectional design, 30 men meet the inclusion criteria and are randomly divided into 3 groups: one month group (1M-G), three months group (3M-G), and six months group (6M-G). Each of the research objects has undergone hemodialysis for one, three and six months. The levels of ferritin, hemoglobin, and erythrocyte count are analyzed with an immunoflourescence method.RESULTS: The Post Hoc LSD analysis states that the ferritin levels of 3M-G (718±63.61) and 6M-G (947±66.22) are significantly higher than that of 1M-G (383.77), p< 0.01. The ferritin level of 6M-G is significantly higher than that of 3M-G, p<0.01. The hemoglobin levels and erythrocyte counts between 1M-G (9.45±0.84) & (3.26±0.55), 3M-G (9.10±1.22) & (3.21±0.50) and 6M-G (8.35±1.21) & (2.92±0.40) are insignificant, p>0.05.CONCLUSION: After undergoing hemodialysis for three and six months, the ferritin levels improve significantly compared to that of one month of hemodialysis, and there is no significant difference in hemoglobin levels and erythrocyte counts.